ISLAM LIBERAL DI INDONESIA: TINJAUAN SOSIOLOGI - Kamaruddin Kamaruddin (JIA (Jurnal Ilmu Agama), 2017)
Liberal Islam Network (JIL), is an organization that carries liberal ideas in Indonesia, encompassing Pluralism, anti-theocracy, supporting democracy and guaranteeing women's rights. JIL emphasizes individual freedom, opens the door of ijtihad in its widest manner by promoting an understanding of context rather than text, and liberates from oppressive social and political structures. JIL discourse is a lot of lurking controversy in Indonesia. JIL discourse is considered to have undermined the understanding of established Islamic teaching (qath'i). Practically, this movement of thought does not see the problems comprehensively. This paper will look at the understanding of JIL in formulating the discourse in terms of the Sociology approach. Conclusively JIL tends to use the Conflict Theory to address the established traditions. This theory is built on three basic assumptions, one of which is the regularity contained in society simply because of pressure or coercion of power from the ruling class, represented by the establishment of the tradition itself